THU0455 Transcriptomics to Identify Synovial Genes and Pathways Associated with Disease Progression in A Cohort of Early Osteoarthritis Patients (CHECK). (10th June 2014) - Blom, A.; van Lent, P.; van den Bosch, M.; Cats, H.; van den Hoogen, F.; Lafeber, F.; van der Kraan, P.; van den Berg, W.
Abstract : Background: If and how the synovial activation that is observed in over 50% of osteoarthritis (OA) patients contributes to irreversible joint pathology, is not known. Objectives: To identify pathways that may determine progression of cartilage damage in this disease. Methods: From 25 patients with knee OA that entered the CHECK Cohort study (Cohort Hip and Cohort Knee) and 6 controls, synovial biopsies were collected at baseline. CHECK is a prospective 10-year follow-up study on participants with early osteoarthritis-related complaints initiated by the Dutch Arthritis Association. Progression was determined based on change of joint space width (JSW) and osteophyte formation in radiographs, as analyzed using the KIDA (Knee Image Digital Analysis) system. Synovial samples from baseline were studied using histology and affymetrix U133-plus-2.0 chips, which were analyzed using Partek Genomics Suite software and DAVID. Results: Histologically, lining thickness and synovitis were enhanced in the CHECK biopsies compared to control synovia. Next we compared synovial tissue of CHECK-patients with radiological damage with CHECK-patients without joint damage at baseline. Among the genes that were strongest associated with cartilage damage were MMP1 (18-fold), MMP3 (10-fold), and S100A8 (6-fold). Immunohistochemical staining revealed that expression of MMP-1 and MMP-3 was highest in the synovial lining layer. Enrichment analysis showed that chemotaxis, innate immune response and MMPs were significantly associated with joint damage at baseline. To determine whether any of the regulated genes and pathways were predictive for progression of joint damage between baseline and t=5 yrs, we identified 13 patients that were marked progressors and 8 non-progressors, based on JSW and osteophyte size. At baseline, neither minimum JSW nor osteophyte size differed between the groups. Approximately 200 genes were expressed more than 2-fold higher in synovium of progressors, versus non-progressors. Among these genes were genes from the wnt-signaling pathway: WISP1, FZD1, FZD8 and FZD10, whereas FRZB was downregulated. In addition, pro-inflammatory factors like IL1, IL6, S100A9 and MMP1 were increased. Macrophage markers like CD14, MHC class II genes, scavenger receptor A3 and CXCR2 were positively associated with progression. This indicates that expression of these factors may predict, or even be involved in, progression of joint damage in OA patients. Using DAVID we identified inflammatory response, macrophage differentiation, blood vessel formation, ossification and cell migration to be enriched in patients that show progression of damage 5 yrs later. Histologically, the progressors showed a higher thickness of the lining layer at baseline compared to non-progressors, 2.0 vs 1.2 respectively on an arbitrary scale from 0-3. Conclusions: These data reveal an active role for the synovium in OA pathology, and identify pathways that may be involved. From histology and the expression data, it appears that presence of macrophages is associated with progression of joint damage in OA. In addition, synovial expression of wnt-signaling genes seems important in progression of damage. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2125